A comparison of antrafenine and aspirin on platelet aggregation and frusemide-induced diuresis. Issue 675 (January 1982) - Hassan, S. M.; Olivesi, A.; Fish, A.; Turner, P.
Abstract : The effects of antrafenine were compared with aspirin and placebo on platelet aggregation and on the diuretic action of frusemide in normal volunteers. Aspirin significantly reduced platelet aggregation at 3 and 6 hr after administration, but antrafenine only at 3 hr. Only aspirin significantly reduced the increase in urine sodium and potassium produced by frusemide.